Effect of Omega-3 on Recurrent Aphthous Stomatitis and Improvement Quality of Life - Zahra Hadian; Ali Akbar Moghadamnia; Sohrab Kazemi; Atena Shirzad (International Journal of Dentistry)
Objective. Recurrent aphthous stomatitis is one of the most common chronic inflammatory diseases in oral mucosa. Beneficial effects of omega-3 supplements on some inflammatory diseases have been proved. The aim of present study was to evaluate the effect of omega-3 supplements in recurrent aphthous stomatitis management and improve oral health-related quality of life. Methods. In this double-blind clinical trial, 40 patients with minor recurrent aphthous stomatitis were randomly divided into case and control groups. The case group received 1000 mg capsules of omega-3, while the control group received placebo capsules for 6 months. The questionnaires of the ulcer severity score and the chronic oral mucosal disease questionnaire were filled by the patients in three steps, at the baseline session, after 3 months, and after 6 months. The data were analyzed by SPSS 22 software through ANOVA, Mann–Whitney, and chi-square tests. P<0.05 was considered as significant. Results. In the omega-3 group, the ulcer severity score showed significant reduction by three-month and six-month follow-ups (P<0.0001, P<0.0001, respectively). The mean score of the chronic oral mucosal disease questionnaire significantly improved by three-month and six-month follow-ups in the omega-3-receiving group. Conclusion. Use of omega-3 oral supplements decreased the severity of aphthous ulcer and improved oral health-related quality of life.